'The School Must Not Be Partisan!' Mobilising against 'Gender Ideology' in Italian Schools - Paolo Gusmeroli; Luca Trappolin (Gender a Výzkum, 2024)
Over the past decade, the protest against so-called 'gender ideology' in Italian schools has witnessed widespread and pervasive mobilisations. Prompted by the directives of anti-gender organisations, grassroots networks activated at the local level have opposed educational programmes related to gender equality, sexuality and the prevention of discrimination against LGBT+ individuals. Through qualitative interviews with Catholic mothers and teachers who participated in the anti-gender conferences in 2015, we adopted a micro-level perspective to interpret their narratives as strategies aimed at defending their ethical and heteronormative educational competence against emerging norms of sexual democracy. The analysis shows how these women position themselves and construct their opposition to gender ideology as a means of asserting social and cultural legitimacy against the perceived risk of symbolic marginalisation in the ﬁeld of education.